EKSPLORASI ETNOMATEMATIKA PADA KUFI MURABBA’ MASJID AL-MULTAZAM CHERRY FIELD BANDUNG - Didi Suhaedi; Maulida Isfahany Fajry; Tia Purniati (ALGORITMA: Journal of Mathematics Education, 2026)
Abstract Proportion and symmetry are important topics in school mathematics, but in fact, they are still difficult for some students to master. One cause is that the learning is not contextual and lacks relevance to students' everyday lives. This study aims to explore ethnomathematics in the Kufi Murabba’ facade of the Al-Multazam Mosque in Cherry Field Bandung, as an alternative source of mathematics learning that is close to the students. The research employed ethnographic methods. Data were collected through observation, interviews, and documentation, and analyzed using triangulation techniques to obtain valid data. The research results show that the Kufi Murabba’ on the facade of Al-Multazam Cherry Field Bandung Mosque contains geometric elements, which are relevant as a learning context for students on the topics of proportion and symmetry. Thus, the Kufi Murabba’ on the facade of Al-Multazam Cherry Field Bandung Mosque can be used as a learning resource for proportion and symmetry. The use of Kufi calligraphy makes learning more contextual, interactive, and meaningful, helping students master the material better and enhancing appreciation of local culture. Abstrak Proporsi dan simetri merupakan materi penting dalam matematika sekolah, tetapi faktanya masih sulit dikuasai oleh sebagian siswa. Salah satu penyebabnya adalah pembelajaran yang belum  kontekstual dan kurang relevan dengan konteks kehidupan sehari-hari siswa. Penelitian ini bertujuan untuk melakukan eksplorasi etnomatematika pada Kufi Murabba’ fasad Masjid Al-Multazam Cherry Field Bandung, sebagai alternatif sumber belajar matematika yang dekat dengan siswa. Penelitian dilakukan menggunakan metode etnografi. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, serta dianalisis menggunakan teknik triangulasi sehingga diperoleh data yang valid. Hasil penelitian menunjukkan bahwa Kufi Murabba’ fasad Masjid Al-Multazam Cherry Field Bandung memiliki unsur-unsur geometris yang relevan sebagai konteks belajar bagi siswa pada materi proporsi dan simetri. Dengan demikian, Kufi Murabba’ pada fasad Masjid Al-Multazam Cherry Field Bandung dapat digunakan sebagai sumber belajar tentang proporsi dan simetri. Penggunaan kaligrafi kufi tersebut membuat pembelajaran lebih kontekstual, interaktif dan bermakna, sehingga membantu siswa menguasai materi dengan lebih baik serta meningkatkan apresiasi terhadap budaya lokal.